2023
DOI: 10.1021/acs.langmuir.2c03035
|View full text |Cite
|
Sign up to set email alerts
|

Potassium-Derived Charge Channels in Boron-Doped g-C3N4 Nanosheets for Photocatalytic NO Oxidation and Hydrogen Evolution

Abstract: The application of graphitic carbon nitride (g-C3N4) in photocatalytic NO oxidation was limited due to severe recombination of photogenerated carriers and low concentration of oxidizing species. In this work, K and B were introduced into the interlayer and in-plane framework of g-C3N4 to address this challenge through the thermal polymerization process. The synthesized K-doped B-g-C3N4 nanosheets exhibited expanded light absorption and low charge recombination efficiency. In addition, the doping of K and B red… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 41 publications
(88 reference statements)
0
5
0
Order By: Relevance
“…UV–vis DRS was performed to characterize the light absorption ability of the prepared samples; accordingly, the effects of B doping and the cyano group on the light absorption ability of g-C 3 N 4 were studied. As shown in Figure a, after B doping and introduction of the cyano group, the intrinsic absorption capacity caused by π → π* electron transition in heptazine rings increased with the boric acid dosage. , In addition, compared with CNN nanosheets, BCNT porous nanotubes exhibited a progressive red shift. Based on the DRS data, the calculated bandgaps of all samples are presented in Figure b.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…UV–vis DRS was performed to characterize the light absorption ability of the prepared samples; accordingly, the effects of B doping and the cyano group on the light absorption ability of g-C 3 N 4 were studied. As shown in Figure a, after B doping and introduction of the cyano group, the intrinsic absorption capacity caused by π → π* electron transition in heptazine rings increased with the boric acid dosage. , In addition, compared with CNN nanosheets, BCNT porous nanotubes exhibited a progressive red shift. Based on the DRS data, the calculated bandgaps of all samples are presented in Figure b.…”
Section: Resultsmentioning
confidence: 95%
“…Energy shortage and environmental degradation are two major global problems that can be solved by the development of renewable and clean energy . Hydrogen energy, known as the “ultimate energy source” can be revolutionary owing to its high energy density and nonpolluting nature. The efficient conversion of solar into hydrogen energy has become a research focus in the field of renewable energy. Graphitic carbon nitride is a promising photocatalytic material for hydrogen evolution, which has been widely studied in recent years. Accordingly, a series of modification strategies have been explored to improve its performance, such as crystal structure engineering, composite structure design, morphology control, , and defect creation. ,, …”
Section: Introductionmentioning
confidence: 99%
“…The K-Co/CNNs showed a significant chemical shift of the major C 1s and N 1s peaks compared to the CNNs, which indicated there were strong interactions between the C or N atoms of the tri-s-triazine and K. In addition, the binding energies of K 2p were 295.54 eV (K 2p 1/2 ) and 292.80 eV (K 2p 3/2 ), respectively (Fig. S2C †), 43,44 which indicated that K formed K-C and K-N bonds. According to Fig.…”
Section: Methods and Modelsmentioning
confidence: 97%
“…5−7 Compared with the traditional TiO 2 photocatalyst, g-C 3 N 4 possesses the ability to utilize visible light, which greatly improves the photocatalytic efficiency. 8 Currently, g-C 3 N 4 is widely used in H 2 evolution, 9 NO removal, 10 O 2 production, 11 H 2 O 2 evolution, 12 and CO 2 reduction. 13 In addition, it can also effectively activate molecular oxygen, which can achieve the photocatalytic conversion of organic groups and the photocatalytic degradation of organic pollutants.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Thus, the development of new renewable energy as an alternative to petroleum resources becomes imperative. , Recently, photocatalysts have been investigated as environmental friendly materials to transform solar energy into usable energy on the earth. , Graphitic carbon nitride (g-C 3 N 4 ), as a two-dimensional layered metal-free polymer with various excellent characteristics including availability, low cost, nontoxicity, and chemical stability, shows great potential in the field of photocatalysis. Compared with the traditional TiO 2 photocatalyst, g-C 3 N 4 possesses the ability to utilize visible light, which greatly improves the photocatalytic efficiency . Currently, g-C 3 N 4 is widely used in H 2 evolution, NO removal, O 2 production, H 2 O 2 evolution, and CO 2 reduction . In addition, it can also effectively activate molecular oxygen, which can achieve the photocatalytic conversion of organic groups and the photocatalytic degradation of organic pollutants. , However, owing to the high-speed recombination of photogenerated electron–hole pairs and limited surface area, the practical application of g-C 3 N 4 is dramatically restricted. , …”
Section: Introductionmentioning
confidence: 99%